«Велике переселення»: театральні будівлі Харкова кінця 1930-х років - Полякова, Юліана Юріївна (Харків, 2021)
Стаття присвячена історії будівництва та використання театральних будівель у Харкові у першій половині XX століття. Авторка аналізує причини виникнення та ліквідації театрів і приміщень, де вони працювали.
The article is devoted to the history of construction and use of theater buildings in Kharkiv in the first half of the twentieth century. The author analyzes the reasons for the emergence and liquidation of theaters and premises where they worked.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Theatre; архітектура; театр; театральні споруди; авангард; Харків; architecture; theater; theater buildings; avant-garde; Kharkiv